2023
DOI: 10.1007/s00167-023-07517-6
|View full text |Cite
|
Sign up to set email alerts
|

Higher age and present injury at the start of the season are risk factors for in‐season injury in amateur male and female football players—a prospective cohort study

Sofi Sonesson,
Hanna Lindblom,
Martin Hägglund

Abstract: Purpose To describe the injury prevalence, injury pattern, and potential baseline risk factors for injuries in male and female adolescent and adult amateur football players. Methods This prospective study followed adolescent and adult amateur football players over one season March–October 2020. The study was completed by 462 players (130 men, age 20.0 ± 5.7, 14–46 years) who answered a baseline survey and a weekly web survey during the season. A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Injury and inadequate rehabilitation are risk factors for re-injury in professional football [40]. Studies from Scandinavia have shown re-injury rates of between 22 and 30% among professional players [41].…”
Section: Re-injuriesmentioning
confidence: 99%
“…Injury and inadequate rehabilitation are risk factors for re-injury in professional football [40]. Studies from Scandinavia have shown re-injury rates of between 22 and 30% among professional players [41].…”
Section: Re-injuriesmentioning
confidence: 99%